Opportunities to reduce medication regimen complexity - Witticke, Diana; Seidling, Hanna; Lohmann, Kristina; Send, Alexander Francesco Josef; Haefeli, Walter E. (Drug safety, 2013)
Numerous characteristics of a medication regimen can weaken patient adherence to drug therapy and thus impair clinical outcomes of drug therapy.
Published online: 8 December 2012
Gesehen am 18.11.2021